A Study of Relationship between Spiritual Leadership and Affective Commitment in Healthcare Industry - Nageeta Tara Rosa; Muhammad Arif; Adrian Irnanda Pratama (Politeknik Negeri Bengkalis, 2023)
This current research examines the influence of spiritual leadership in affective commitment through calling and membership. This research uses a sample of 110 employees either interact or experience direct policies toward the leader with a minimum of 2 years working period at Zainab Mother and Child Hospital in Pekanbaru, Riau Province. Simple Linear Regression is used in this study to measure the contribution toward the dependent variable by using the IBM SPSS version 20. The analysis then shows the results that calling and membership derived from the concept of spiritual leadership have a significant effect on affective commitment. Calling significantly influences affective commitment, and it is similar to membership, which has significant value relates to affective commitment. Recommendations for leaders, employees, and future research are discussed.